CD31-positive microvessel density within adenomas of Lynch Syndrome patients is similar compared to adenomas of non-Lynch patients - Vleugels, Jasper L.A.; van Neerven, Sanne M.; van Leerdam, Monique E.; Wanders, Linda K.; de Wit, Meike; Carvalho, Beatriz; Delis-van Diemen, Pien M.; Kallenberg, Frank G.J.; Vermeulen, Louis; Beliën, Jeroen A.; East, James E.; Meijer, Gerrit A.; Dekker, Evelien (Endoscopy International Open, 2019)
Background and study aims Microsatellite instability accelerates colorectal cancer development in patients with Lynch syndrome (LS). Previous research showed that virtual chromoendoscopy increases detection of adenomas during colonoscopy surveillance of patients with LS. Because previous research revealed that Lynch patients have an increased vascular network in the oral mucosa, we hypothesized that increased vascularization of LS-associated adenomas is the cause of better detection with virtual chromoendoscopy.Patients and methods In this pilot study, patients with LS having a proven germline mutation were selected from two tertiary referral hospitals and non-LS patients from an outpatient colonoscopy center. Adenomas from patients with LS were exactly matched in size and histology with adenomas from non-LS patients. Initial adenoma diagnosis was confirmed by a specialist pathologist. All adenomas were stained with CD31 and adenomatous tissue was annotated by the specialist pathologist. Image analysis of CD31-positive microvessel density was conducted using FIJI software. Results Colonoscopy of 63 patients with LS and 24 non-LS patients provided 40 adenomas that could be exactly matched in size and histology. In image-analysis, the CD31-positive microvessel density (2.49 % vs. 2.47 %, P = 0.96), the average size of CD31-positive structures (514 μm2 vs. 523 μm2, P = 0.26) nor the amount of vascular structures per mm2 (183 vs. 176, P = 0.50) differed between adenomas of LS patients and non-Lynch patients. Conclusion The outcomes of this pilot case-control study did not provide further insights into the mechanism of increased adenoma detection in LS patients using virtual chromoendoscopy techniques.